2020
DOI: 10.1007/s00268-020-05384-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Antisepsis with Chlorhexidine Versus Povidone‐Iodine for the Prevention of Surgical Site Infection: a Systematic Review and Meta‐analysis

Abstract: Background and Objective Chlorhexidine (CH) and povidone-iodine (PI) are the most commonly used preoperative skin antiseptics at present. However, the prevention of the surgical site infection (SSI) and the incidence of skin adverse events do not reach a consistent statement and conclusion. This meta-analysis aimed to evaluate the efficacy of chlorhexidine and povidone-iodine in the prevention of postoperative surgical site infection and the incidence of corresponding skin adverse events. Method Substantial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…A wide spectrum of paint solutions, including both alcohol-and non-alcohol-based agents, have been certified for this purpose [106], but evidence for a particular product is limited. A recent systematic review and meta-analysis found superior benefit for chlorhexidine compared to povidone-iodine in clean surgery in terms of prevention of postoperative SSIs (risk ratio 0.81; 95% CI, 0.67-0.98) [107]. Concerns persist, however, regarding the effective concentration of chlorhexidine, given a report stating that even with 4% chlorhexidine, skin bacteria could still be cultivated from healthy volunteers [108].…”
Section: Preparation Of Operative Fieldmentioning
confidence: 99%
“…A wide spectrum of paint solutions, including both alcohol-and non-alcohol-based agents, have been certified for this purpose [106], but evidence for a particular product is limited. A recent systematic review and meta-analysis found superior benefit for chlorhexidine compared to povidone-iodine in clean surgery in terms of prevention of postoperative SSIs (risk ratio 0.81; 95% CI, 0.67-0.98) [107]. Concerns persist, however, regarding the effective concentration of chlorhexidine, given a report stating that even with 4% chlorhexidine, skin bacteria could still be cultivated from healthy volunteers [108].…”
Section: Preparation Of Operative Fieldmentioning
confidence: 99%
“…This correlation appears to be especially relevant considering that, despite skin disinfection with povidone-iodine solution, the majority of implant sites in our study were contaminated prior to implantation. Based on the observations reported in our work and other clinical studies which describe higher wound infection rates using povidone-iodine solution for surgical antisepsis, as compared to a chlorhexidine solution, a chlorhexidine-based skin disinfectant should be considered as antiseptic of choice in future studies 23 .…”
Section: Limitationsmentioning
confidence: 69%
“…The dressings we prepared (with PVA-HPMC, as with other combinations described in the literature) are characterized by enhanced properties, i.e., swelling or flexibility relative to pure PVA [ 40 , 41 ]. Povidone-iodine (PVP-I) was selected as the active drug in films, as it displays the broadest spectrum of antimicrobial effects against bacteria, yeasts, molds, other fungi, and certain viruses, and at the same time, microbes lack resistance to the compound [ 42 , 43 , 44 , 45 , 46 ]. Kaeviad et al developed dental floss impregnated with PVP-I as a drug antimicrobial delivery system against periodontopathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%